Factors affecting Chinese farmers' microcredit participation. Issue 1 (4th February 2019) - Qin, Ming; Wachenheim, Cheryl Joy; Wang, Zhigang; Zheng, Shi
Abstract : Purpose: The purpose of this paper is to investigate factors affecting use of microcredit among farmers in Northern China. Design/methodology/approach: A two-stage Heckman model is used to estimate the effect of farmer and family characteristics and loan and lending environment on likelihood of farmer participation in microcredit and the value of loans taken. Data from 342 first-hand observations in Northern China were used. Findings: Social capital, production cost, non-labor family members, income, guarantee group membership, village head loan guarantee, and messenger use were found to increase use of microcredit. The same factors were found to affect the value of loans among participating farmers except a guarantor requirement for the loan replaces membership in a guarantee group. Practical implications: Results support that there is demand for microcredit among farmers and that they are willing to take steps to obtain it including seeking membership in a household guarantee group. Identification of faced constraints facilitates understanding of supply-side efforts with potential to decrease financial exclusion with a focus on external-to-market intervention. Originality/value: Pivotal findings are the importance of guarantee group membership for loan approval and that this requirement hinders farmers' ability to obtain credit. Three alternatives are suggested to overcome this constraint including excluding low-risk borrowers from a group guarantee requirement; charging higher interest rates on high risk loans not supported by a guarantee; and development of insurance options to replace the guarantee.